2016
DOI: 10.14744/anatoljcardiol.2015.6593
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc-HS score in non-ST elevation acute coronary syndrome patients: assessment of coronary artery disease severity and complexity and comparison to other scoring systems in the prediction of in-hospital major adverse cardiovascular events

Abstract: Objective:We recently described the CHA2DS2-VASc-HS score as a novel predictor of coronary artery disease (CAD) severity in stable CAD patients. We aimed to assess the accuracy of the CHA2DS2-VASc-HS score in the determination of CAD severity and complexity and its availability in the risk stratification of in-hospital major adverse cardiovascular events (MACE) in non-ST elevation acute coronary syndrome (NSTE-ACS) patients.Methods:We prospectively analyzed the clinical and angiographic data of consecutive NST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…In a similar study Taºolar, et al found 23.2% patients with cardiac events in patients with CHA2DS2-VASc-HS >4 compared to 3.8% in score ≤4. 16 The findings of this study were consistent with the previous study. Risk was measured by relative risk (RR).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a similar study Taºolar, et al found 23.2% patients with cardiac events in patients with CHA2DS2-VASc-HS >4 compared to 3.8% in score ≤4. 16 The findings of this study were consistent with the previous study. Risk was measured by relative risk (RR).…”
Section: Discussionsupporting
confidence: 93%
“…Total cholesterol and triglyceride level had higher in group II than group I but did not reach the level of significance (p>0.05). 16 HDL cholesterol was lower in group I than group II with no statistical difference. Among biochemical parameters only cardiac troponin level were found higher in group I compared to group II and reached the level of significance.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Many studies have used the CHA 2 DS 2 -VASc-HS score on coronary heart disease, as the study by Cetin et al (2014) found that the CHA 2 DS 2 -VASc-HS score > 2 was a predictor of coronary heart disease severity. 9 The same study was developed by Tasolar et al (2016) also mentioned that the CHA 2 DS 2 -VASc-HS score > 5 could be a predictor of severity and complexity of coronary artery disease and predictors of major cardiovascular events in NSTEMI patients. 17 Both of these studies were important and significant because the components in the CHA 2 DS 2 -VASc-HS score which were hypertension, older age, diabetes mellitus, male gender, hyperlipidemia and smoking are very important traditional risk factors for coronary heart disease and are prognostic factors in cardiovascular outcome.…”
Section: Discussionmentioning
confidence: 92%
“…7 CHA 2 DS 2 -VASc score was also widely used to predict severity and outcome of coronary artery disease with or without AF. [14][15][16] CHA 2 DS 2 -VASc score has also been applied in PE. A total of 73,541 adults with AF and without PE were followed-up for 1 year.…”
Section: Discussionmentioning
confidence: 99%